2008
DOI: 10.1021/bi800773f
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Cyanine 5 Terminally Attached to Double-Stranded DNA: Implications for FRET Studies

Abstract: Fluorescence resonance energy transfer, FRET, can be used to obtain long-range distance information for macromolecules and is particularly powerful when used in single-molecule studies. The determination of accurate distances requires knowledge of the fluorophore position with respect to the macromolecule. In this study we have used NMR to determine the structure of the commonly used fluorophore indocarbocyanine-5 (Cy5) covalently attached to the 5'-terminus of double-helical DNA. We find that Cy5 is predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
97
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 35 publications
(49 reference statements)
8
97
0
Order By: Relevance
“…Therefore, we took advantage of the FRET effect of the common Cy3/Cy5 fluorophore pair in single-molecule fluorescence studies, which involves nucleic acids. 32 FRET is a powerful tool for retrieving information on molecular proximity, orientation, and confirmation on the nm scale from samples. 33 By applying double-labeled oligonucleotides with Cy3 as the donor on the 3′-end and Cy5 as the acceptor on the 5′-end of the oligonucleotide sequence, first experiments with pure oligonucleotides, that means without encapsulation and without the presence of cells, were performed via fluorescent measurements ( Figure S9).…”
Section: Fret Measurementsmentioning
confidence: 99%
“…Therefore, we took advantage of the FRET effect of the common Cy3/Cy5 fluorophore pair in single-molecule fluorescence studies, which involves nucleic acids. 32 FRET is a powerful tool for retrieving information on molecular proximity, orientation, and confirmation on the nm scale from samples. 33 By applying double-labeled oligonucleotides with Cy3 as the donor on the 3′-end and Cy5 as the acceptor on the 5′-end of the oligonucleotide sequence, first experiments with pure oligonucleotides, that means without encapsulation and without the presence of cells, were performed via fluorescent measurements ( Figure S9).…”
Section: Fret Measurementsmentioning
confidence: 99%
“…1 It has been widely used for measuring the distance between two fluorophores. [2][3][4] However, as a spectroscopic ruler conventional FRET suffers from a limited length scale of approximately 10 nm. Plasmonic structures provide a route towards longer range non-radiative energy transfer (NRET) via nanometal surface energy transfer (NSET) or localised surface plasmon (LSP) coupled FRET.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier NMR studies have shown that when these are attached to the 5Ј termini of duplex DNA via a 3-carbon linker to the 5Ј-phosphate they are predominantly stacked onto the ends of the helix in the manner of an additional base pair (11,26). This would provide a favorable situation in which the orientation dependence of FRET could be observed, and we have therefore studied a series of DNA and DNA-RNA hybrid duplexes to seek this effect.…”
mentioning
confidence: 99%
“…Although this is a good approximation for freely mobile fluorophores like fluorescein that are terminally attached to double-stranded nucleic acids, it is rather less probable for cyanine dyes in this situation. By using NMR we have shown that Cy3 and Cy5 are predominantly stacked onto the end of dsDNA when coupled to the 5Ј-terminal phosphates via C 3 linkers (11,26) (Fig. 1 C and D).…”
mentioning
confidence: 99%
See 1 more Smart Citation